2019
DOI: 10.2169/internalmedicine.2608-18
|View full text |Cite
|
Sign up to set email alerts
|

Proton-pump Inhibitor-induced Severe Hypomagnesemia and Hypocalcemia are Clinically Masked by Thiazide Diuretic

Abstract: Hypomagnesemia, a side effect of proton-pump inhibitors (PPIs), can be asymptomatic. The presence of hypocalcemia or hypokalemia is indicative of hypomagnesemia; however, the concomitant use of PPIs and thiazide may mask hypocalcemia. A 79-year-old woman with a history of chronic heart failure and chronic kidney disease developed symptomatic hypocalcemia and hypomagnesemia. Five weeks earlier, she had developed thiazide-induced hyponatremia, so thiazide had been discontinued. Reviewing the patient's charts rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 20 publications
0
11
0
3
Order By: Relevance
“…Hypocalcemia may develop following hypomagnesemia and is thought to be caused by the inhibitory effect of hypomagnesemia on parathyroid gland hormone secretion [ 14 ]. The observation of asymptomatic hypokalemia or hypocalcemia in patients treated with PPIs is often indicative of hypomagnesemia [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hypocalcemia may develop following hypomagnesemia and is thought to be caused by the inhibitory effect of hypomagnesemia on parathyroid gland hormone secretion [ 14 ]. The observation of asymptomatic hypokalemia or hypocalcemia in patients treated with PPIs is often indicative of hypomagnesemia [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 40% of calcium is bound to albumin and is tightly regulated by PTH and vitamin D. Hypomagnesemia is a common electrolyte disturbance that occurs in up to 12% of hospitalized patients and up to 60 to 65% of patients in the intensive-care unit [ 5 , 6 ]. The causes of hypocalcemia vary, with impaired production of PTH and vitamin D being the most common.…”
Section: Discussionmentioning
confidence: 99%
“…Thiazides reduce the expression of magnesium channels in the epithelium of the distal renal tubules, witch are called TRPM6 (Transient Receptor Potential Cation Channel Subfamily M Member 6), increasing renal magnesium excretion 10,13 . Thiazides, however, are able to decrease calciuria and may reduce the severity of hypocalcemia induced by hypoparathyroidism triggered by hypomagnesemia 10,14 . In most patients who use thiazides alone, hypomagnesemia is not a frequent abnormality and serum magnesium monitoring is not recommended 10 .…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
“…However, when a proton pump inhibitor (PPIs) is associated to a thiazide, greater caution is needed. Uehara et al 14 identified a 42% increase in the prevalence of hypomagnesemia in users of thiazides concomitantly with PPIs, when compared to the isolated use of thiazides. Intestinal magnesium absorption depends on a passive and an active transport mechanism 4 .…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%